1997
DOI: 10.2175/106143097x125164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tertiary filtration and disinfection systems for upgrading high‐purity oxygen‐activated sludge plant effluent

Abstract: The Joint Water Pollution Control Plant (JWPCP) of the Sanitation Districts of Los Angeles County provides advanced primary and partial secondary treatment for 15.3 m 3 /s (350 MGD) of wastewater. A 7-mo pilot plant study evaluated several tertiary treatment alternatives for in-plant water reuse. The influent to the tertiary treatment system was the high-purity oxygen-activated sludge plant effluent. Three filtration systems were evaluated: a deep-bed anthracite filter. a shalIowdepth pulsed-bed sand filter, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A seven-month pilot-plant study in Los Angeles County (California) evaluated three filtration systems for water reuse using high-purity oxygen-activated sludge plant effluent: a deepbed anthracite filter, a shallow depth pulsed-bed sand filter and a continuous backwash deep-bed sand filter. All three filters were capable of consistently meeting the State of California's effluent turbidity limit and were characterized by similar costs (Kuo et al, 1997). Field-scale evaluation of gravel-bed hydroponic wetlands in Egypt demonstrated the capacity for removing eggs of human parasites and producing effluents which met the World Health Organization (WHO) microbiological guidelines for reuse (Stott et al, 1997).…”
Section: Emissions and Wastewater Managementmentioning
confidence: 99%
“…A seven-month pilot-plant study in Los Angeles County (California) evaluated three filtration systems for water reuse using high-purity oxygen-activated sludge plant effluent: a deepbed anthracite filter, a shallow depth pulsed-bed sand filter and a continuous backwash deep-bed sand filter. All three filters were capable of consistently meeting the State of California's effluent turbidity limit and were characterized by similar costs (Kuo et al, 1997). Field-scale evaluation of gravel-bed hydroponic wetlands in Egypt demonstrated the capacity for removing eggs of human parasites and producing effluents which met the World Health Organization (WHO) microbiological guidelines for reuse (Stott et al, 1997).…”
Section: Emissions and Wastewater Managementmentioning
confidence: 99%
“…An extensive menu of technologies is available to choose from to meet project specific goals. Kuo et al (1997) reported on the results of a 7-month, pilot-plant study in Los Angeles County, California, which evaluated three filtration systems for in-plant water reuse using high-purity oxygen-activated sludge plant effluent: a deep-bed anthracite filter, a shallow-depth pulsed-bed sand filter, and a continuous backwash deep-bed sand filter. Chlorination and ultraviolet (UV) disinfection were also compared.…”
Section: Planning and Managementmentioning
confidence: 99%
“…However, bubble transfer is the predominant means of oxygen transfer. So far, considerable research interests have been focused on the enhancement of the bubble transfer efficiency by developing a wide variety of new aeration techniques, including the utilization of high-purity-oxygen aeration system [4][5][6][7][8][9][10], deep aeration system [11][12][13] and fine bubble diffuser [14][15][16][17], etc. Nevertheless, only a little effort has been devoted to the research on the improvement of surface transfer efficiency.…”
Section: Introductionmentioning
confidence: 99%